In Support of Unfinished Inclusion - Hausstätter, R.S. (Scandinavian Journal of Educational Research, 2014)
This article claims that the radical potential inherent in the origins of inclusive education has been altered into a tool for protecting the status quo. Drawing on ideas from the essay 'The Unfinished' by Thomas Mathiesen (1971), I discuss inclusion as a potential alternative to mainstream education and argue that the potential power of change in this alternative view of schooling is greatly reduced because the inclusion movement, as it is appears today, tends to offer finished solutions. To create a viable alternative to mainstream education requires an understanding of unfinished inclusion because this opens an uncertainty within education that may make the established system more open to change. The unfinished will in this way restore the disruptive potential of inclusive education. © 2013 © 2013 Scandinavian Journal of Educational Research.